The role of the hypothalamic-pituitary-adrenal axis in depression across the female reproductive lifecycle: current knowledge and future directions - Hantsoo, Liisa; Jagodnik, Kathleen M.; Novick, Andrew M.; Baweja, Ritika; di Scalea, Teresa Lanza; Ozerdem, Aysegul; McGlade, Erin C.; Simeonova, Diana I.; Dekel, Sharon; Kornfield, Sara L.; Nazareth, Michelle; Weiss, Sandra J. (Frontiers in Endocrinology, 2023)
The aim of this narrative review is to consolidate knowledge on the role of the hypothalamic-pituitary-adrenal (HPA) axis in depression pathophysiology at different reproductive stages across the female lifespan. Despite growing evidence about the impact of gonadal hormones on mood disorders, no previous review has examined the interaction between such hormonal changes and the HPA axis within the context of depressive disorders in women. We will focus on HPA axis function in depressive disorders at different reproductive stages including the menstrual cycle (e.g., premenstrual dysphoric disorder (PMDD)), perinatally (e.g., postpartum depression), and in perimenopausal depression. Each of these reproductive stages is characterized by vast physiological changes and presents major neuroendocrine reorganization. The HPA axis is one of the main targets of such functional alterations, and with its key role in stress response, sets the tone for vulnerable windows for depression across the female lifespan. We begin with an overview of the HPA axis and a brief summary of techniques for measuring HPA axis parameters. We then describe the hormonal milieu of each of these key reproductive stages, and integrate information about HPA axis function in depression across these reproductive stages, describing similarities and differences. The role of a history of stress and trauma exposure as a contributor to female depression in the context of HPA axis involvement across the reproductive stages will also be presented. This review advances the pursuit of understanding common biological mechanisms across depressive disorders among women. Our overarching goal is to identify unmet needs in characterizing stress-related markers of depression in women in the context of hormonal changes across the lifespan, and to support future research in women's mental health as it pertains to pathophysiology, early diagnosis, and treatment targets.